Imunidade celular em caninos neonatos - do nascimento ao 45° dia de idade - Klein, R. P.; Lourenço, M. L. G. [UNESP]; Moutinho, F. Q. [UNESP]; Takahira, R. K. [UNESP]; Lopes, R. S. [UNESP]; Martins, R. R.; Machado, L. P.; Silveira, V. F.; Ferreira, H. [UNESP] (Universidade Federal de Minas Gerais, Escola de Veterinária, 2014)
The aim of this study was to evaluate the immune development of newborn canines, evaluating the cellular immunity by analysis of leukocyte and lymphocyte totals and sub-population of T lymphocytes (CD4+ and CD8+) by the flow cytometry technique. Thirty neonatal mongrel dogs of both sexes were used, at 3, 10, 17, 24, 31, 38 and 45 days of age. The total leukocyte count to 45 days (11639±3574/µL) was significantly greater than on the third day of age (8740±1812) (p<0.05); There were no differences between the total count of lymphocytes at 45 days in relation to the third day of age. As for the subpopulations of CD4+ and CD8+, CD4+ cell percentages, at three days of age (24.9±16.8) they were inferior when compared to the average between the 10th, 24th and 31st day (35.5), and CD8+ cells, on the third day, were lower compared with averages from the 10th and 31st day of age. It can be concluded that the subpopulations of CD4+ and CD8+ cells undergo oscillations during development, with growing postnatal levels obtained at three days old. The CD4:CD8 ratio showed superiority to the first cell type, and the largest relationship between CD4+ and CD8+ occurred on the third day of age. Based on the results obtained in this study, the differences noted in lymphocyte populations weekly showed the dynamics of these cells during the neonatal period.

O objetivo do presente trabalho foi acompanhar o desenvolvimento imunológico dos neonatos caninos, a fim de avaliar a imunidade celular pela análise dos leucócitos e linfócitos totais e das subpopulações de linfócitos T (CD4+ e CD8+) pela técnica de citometria de fluxo. Foram utilizados 30 cães neonatos de ambos os sexos, sem raça definida, aos três, 10, 17, 24, 31, 38 e 45 dias de idade. A contagem de leucócitos totais aos 45 dias (11.639±3.574) foi significativamente maior que no terceiro dia de idade (8.740±1.812) (P<0,05); não houve diferença entre a contagem total de linfócitos aos 45 dias em relação ao terceiro dia de idade. Quanto às subpopulações de LT CD4+ e LT CD8+, os percentuais de LT CD4+, aos três dias de idade (24,9±16,8%), foram inferiores quando comparados à média entre o 10°, o 24° e o 31°dia (35,5%), e os de CD8+, ao terceiro dia, menores em relação às médias do 10° e do 31° dia de idade. Pode-se concluir que as subpopulações de LT CD4+ e CD8+ sofrem oscilações durante o desenvolvimento pós-natal, sendo estas crescentes em relação aos níveis obtidos aos três dias de idade. A relação CD4+:CD8+ mostrou superioridade para o primeiro tipo celular, sendo que a maior relação entre CD4+ e CD8+ ocorreu no terceiro dia de idade. Com base nos resultados obtidos neste estudo, notaram-se as diferenças semanais nas populações linfocitárias, o que demonstra a dinâmica dessas células durante o período neonatal.
Cellular immunity in canine newborns - from birth to the 45th day of life
Keywords: caninos; células linfocíticas; neonatologia; canines; lymphocytic cells; neonatology